Use of the First Step Program in Preschool - Kholmatova Shakhnoza Khatamorovna (Zien Journals, 2022)
The article provides information, recommendations, and conclusions on the current state of the development of the preschool education system and the reforms that are taking place in the field, and the "First Step” in this process information about the application of the program in preschools.
Keywords: Preschool education; concept; irst step program; child; qualification